Exploring factors that affect the destination brand in tourism industry - CHOI, Yura (KDI School, 2016)
Around the world, tourism industry influenced the economic development greatly (Milne and Ateljevic, 2001). Tourism industry gained more attention by reasons of being most feasible and sustainable economic development advantage, and also earnings of foreign currency (UNWTO, 2016). ‘Destination brand’ as national identity has received attention with a strategy of building a unique identity of destination which makes differentiation (Morrison & Anderson, 2002). The purpose of study is to explore the effects of different perceptions, intention, satisfaction, loyalty, and brand equity in tourism industry. In particular, this study measures the relationships of i) functional, experiential, and symbolic perception on attitude, ii) travelers’ attitude on satisfaction and intention to visit, iii) satisfaction level of travelers’ on loyalty, iv) loyalty on destination brand equity, and v) intention to visit on destination brand equity. This collects data via online survey and in order to prove the hypotheses, this study applied statistical analysis such as factor analysis, Analysis of Variance (ANOVA) and regression analyses. This study provides both theoretical and managerial implication to the public policy.
Thesis(Master) --KDI School:Master of Public Policy,2016